The Effect of Customer Service Communication Strategy and Service Quality on Customer Satisfaction - Rhoni Ilham Tampubolon (ProBisnis : Jurnal Manajemen, 2023)
The purpose of this study was to partially and simultaneously influence customer service and service quality communication strategies on customer satisfaction at the Harapan Indah Jaya Medan Muslim Clothing Store. The population in this study were all customers of the Harapan Indah Jaya Medan Muslim Clothing Store using a sample of 54 people. To obtain data in the preparation of this thesis, the authors use the instrument; documentation studies and interviews (interviews), as well as a questionnaire (questionnaire). In analyzing the data using multiple linear regression, t test, F test and test of determination. Based on the results of the F test results for the variables Communication strategy and Service quality, it can be concluded that the variables Communication strategy and Service quality together have a significant effect on customer satisfaction. Based on the results of the t test, it can be concluded that the communication strategy and service quality variables partially have a significant influence on customer satisfaction. The Adjusted R-Square value obtained is 0.358 indicating about 35.8% of the customer satisfaction variable can be explained by the Communication strategy variable (X1) and Service quality variable (X2). The rest (100% - 35.8% = 64.8%) is influenced by other variables such as facilities, prices, promotions and others which are not examined in this study